Harvesting Alternative Water Resources (U.S. West) - RANDLE, Sayd (Institutional Knowledge at Singapore Management University, 2019)
Since the mid-20th century, the western half of the United States has been known worldwide as a landscape marked by extraordinary water infrastructure. The semi-arid region’s enormous network of dams, reservoirs, and pipelines distributes its freshwater resources among an ever-growing population of residential, industrial, and agricultural users. Since the 1970s, however, growing environmental stresses and water demands have led many of the region’s water managers to look beyond the region’s rivers, lakes, and aquifers to expand the available supply. Wastewater and stormwater, substances previously approached as wastes or hazards in the region’s dominant management paradigms, are now increasingly understood as potential water resources. And saltwater, particularly the Pacific Ocean, is frequently cited as a potential solution to water supply stresses, particularly in densely populated coastal Southern California. The reassessment and exploitation of these waters entail regulatory, governance, political, infrastructural, and cultural challenges, as water managers and residents must rework the laws, institutions, and norms around these substances. Resistance to the new water sources has also arisen within the region, due to concerns about the safety, environmental impacts, and cost of their capture, cleaning, and distribution. This article draws on documents from a wide range of disciplines to explore the complicated (and at times, contentious) process of introducing these new supplies to the US West’s networks of water provision.